Treatment of thyroid disorder supported by 5-phosphodiesterase inhibitors improved erectile dysfunction in patients with hypo- and hyperthyroidism - Broul, Marek; Kučerová, Petra; Jozífková, Eva; Žižková, Kamila (Neuro-endocrinology letters, 2024)
INTRODUCTION: The relationship between a poorly functioning thyroid gland and erectile dysfunction (hereinafter, "ED") has been demonstrated in many studies. If a man has thyroid problems, it can negatively affect his ability to achieve or maintain an erection. The thyroid gland produces hormones that affect metabolism and overall body function, including blood circulation. If the thyroid gland is not functioning properly, it can lead to blood circulation disorders, which can affect erectile function. There are also symptoms of thyroid disorders that can contribute to ED. Some of these symptoms include fatigue, depression, and anxiety, which can negatively affect a man's psychological side and affect his sexual performance. OBJECTIVES AND METHODS: In our article, we present a series of patients with ED who were treated in our department and found to have some form of thyroid dysfunction. RESULTS: After treatment for thyroid dysfunction and treatment with 5-phosphodiesterase inhibitors were implemented, erectile function improved in all patients ((Wilcoxon Signed Rank Test; Z = -4.55; p (2-tailed) < 0.001; n = 27) to the level of mild or no ED. Improvement occurred in men with hyper- and hypothyroidism. After one year of treatment, there was no difference between the two groups (t-test; t = 0.75; df = 0.25; p < 0.46). CONCLUSION: This study shows that screening for thyroid dysfunction should be performed in all men with ED and that treating thyroid dysfunction may be an effective way to improve erectile function in men with these health problems.
Keywords: inhibitory fosfodiesterasy 5; Humans; lidé středního věku; Erectile Dysfunction; Aged; dospělí; erektilní dysfunkce; Hypothyroidism; výsledek terapie; senioři; lidé; Phosphodiesterase 5 Inhibitors; Adult; hypotyreóza; Male; Middle Aged; Treatment Outcome; Hyperthyroidism; mužské pohlaví; hypertyreóza